Strengthening Early Childhood Cognitive Stimulation through Parental Assistance in the Educational Digital Media Ecosystem - Agus Setiawan; Supriyanto Supriyanto; Ihlas Ihlas (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
The rapid development of digital technology has transformed the learning environment of early childhood, creating both opportunities and challenges for cognitive development. While digital media can provide diverse educational resources, its effectiveness largely depends on the quality of parental guidance and supervision. This study aims to examine the strengthening of early childhood cognitive stimulation through parental assistance within an educational digital media ecosystem. The research focuses on how parents facilitate, monitor, and optimize children's interactions with educational digital platforms to support cognitive growth. A qualitative descriptive approach was employed, involving observations, interviews, and documentation with parents and early childhood education stakeholders. The findings reveal that parental involvement plays a crucial role in enhancing children's cognitive abilities, including problem-solving skills, language development, memory retention, creativity, and critical thinking. Educational digital media became more effective when parents actively selected age-appropriate content, provided learning guidance, and encouraged interactive discussions during and after media use. Furthermore, a collaborative ecosystem involving families, educators, and digital learning resources contributed significantly to creating meaningful learning experiences for children. The study concludes that strengthening parental assistance within the educational digital media ecosystem is essential for maximizing the cognitive development potential of early childhood in the digital era while minimizing the negative impacts of uncontrolled media exposure.